One new species of the genus Cyclea Arn. ex Wight (Menispermaceae Juss.) for the flora of Vietnam - Chinh, Vu Tien; Phuong, Vu Xuan (Academia Journal of Biology, 2014)
In the Flora of Vietnam, the genus Cyclea Arn. ex Wight (Menispermaceae Juss.) had 8 species [Pham Hoang Ho, 1999; Nguyen Tien Ban, 2003]. In 2004, Vu Tien Chinh and Vu Xuan Phuong have found one new species for the flora of Vietnam, therefore there were 9 species of Cyclea in Vietnam. During the study of specimens of this genus, we have found one new species (Cyclea sutchuenensis Gagnep.) for the flora of Vietnam; this specimen was kept in the botanical herbarium in Hochiminh city (HM). So, there are 10 species of the genus Cyclea in the flora of Vietnam.